2011
DOI: 10.1097/cmr.0b013e328347ee33
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of VEGF, HIF1-a, and PlGF in malignant melanomas and dysplastic nevi

Abstract: We evaluated the role of vascular endothelial growth factor (VEGF), placental growth factor (PlGF), and hypoxia-inducible factor 1-a (HIF1-a) in melanoma angiogenesis and investigated their expression in dysplastic nevi, as potential melanoma precursors. In addition, we examined a possible correlation of VEGF expression with PlGF and HIF1-a. These factors were detected immunohistochemically in 95 melanomas of all types and stages and in 28 dysplastic nevi. We used 10 intradermal melanocytic nevi as controls. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 22 publications
(60 reference statements)
1
5
1
1
Order By: Relevance
“…We found that 5 out of 81 patients with melanoma (2 in stage I, 2 in stage II and 1 in stage III) were completely negative to VEGF (5.7%). In the study of Konstatina et al 28 from 2011, 13.69% patients with melanoma were negative for VEGF, but, in contrast with our control group results, 75% of patients with dysplastic nevi had weak VEGF staining. The opinions on VEGF positivity in benign melanocytic lesions are divided.…”
Section: Discussioncontrasting
confidence: 90%
“…We found that 5 out of 81 patients with melanoma (2 in stage I, 2 in stage II and 1 in stage III) were completely negative to VEGF (5.7%). In the study of Konstatina et al 28 from 2011, 13.69% patients with melanoma were negative for VEGF, but, in contrast with our control group results, 75% of patients with dysplastic nevi had weak VEGF staining. The opinions on VEGF positivity in benign melanocytic lesions are divided.…”
Section: Discussioncontrasting
confidence: 90%
“…Similarly, targeting HIF-1α-related pathways may attenuate cardiovascular and metabolic consequences of IH ( 46 – 50 ). Thus, it is reasonable to assume that increased HIF-1α expression in the context of sleep-disordered breathing in our cohort would lead to increased HIF-1α expression in tissues in general and more specifically in the CM lesions, where its transcriptional activity could have fostered increased proliferation and other aggressiveness indicators ( 14 – 16 ). In contrast, the absence of any significant association between VEGF expression in the CM sections and correlates of nocturnal hypoxemia was surprising.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, high expression levels of HIF‐1α, HIF‐2α and their target genes such as VEGF, have also been detected in melanoma cells in up to 80% cases of primary and metastatic melanoma specimens from patients, and more particularly at the margin of necrotic areas of tumours, and associated with melanoma progression as well as a poor prognosis of patients . Moreover, a nuclear staining for pluripotency‐associated transcription factor Oct‐3/4 was also seen in a small subset of melanoma cells, and particularly in hypoxic cancer cells near necrotic areas within primary melanomas in vertical growth phase or metastatic melanoma tissue specimens .…”
Section: Functions Of Hypoxia and Hifs In The Development Of Melanomamentioning
confidence: 99%